2015
DOI: 10.1007/s10787-015-0240-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NO–cGMP pathway in anti-hyperalgesic effect of PDE5 inhibitor tadalafil in experimental hyperalgesia

Abstract: The association of elevated level of cyclic guanosine monophosphate (cGMP) with inhibition of hyperalgesia and involvement of nitric oxide (NO)-cGMP pathway in the modulation of pain perception was previously reported. Phosphodiesterases 5 (PDE5) inhibitors, sildenafil and tadalafil (TAD) used in erectile dysfunction, are known to act via the NO-cGMP pathway. TAD exerts its action by increasing the levels of intracellular cGMP. Hence, the present study investigated the effect of TAD 5, 10, or 20 mg/kg, per os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Groups receiving lodenafil carbonate showed significantly reduced thermal hyperalgesia and displayed total reversal of mechanical hyperalgesia from 30 minutes after treatment until the end of test, which paralleled the effect seen with 300 mg/kg (1665 μmol/kg) of acetylsalicylic acid. Comparable results were previously described either for sildenafil, vardenafil or tadalafil, [9][10][11] and their blockade by L-NAME was also reported, reinforcing the importance of the NO/cGMP pathway for the observed effects.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Groups receiving lodenafil carbonate showed significantly reduced thermal hyperalgesia and displayed total reversal of mechanical hyperalgesia from 30 minutes after treatment until the end of test, which paralleled the effect seen with 300 mg/kg (1665 μmol/kg) of acetylsalicylic acid. Comparable results were previously described either for sildenafil, vardenafil or tadalafil, [9][10][11] and their blockade by L-NAME was also reported, reinforcing the importance of the NO/cGMP pathway for the observed effects.…”
supporting
confidence: 84%
“…1 These effects led to an initial interest in PDE5 as therapeutic target, directing the clinical use of PDE5-selective inhibitors in erectile dysfunction and pulmonary hypertension. 6,7 The antinociceptive action of PDE5 inhibitors is already known and inhibition of either guanylyl cyclase (GC), PKG or K + channels abolishes this effect, [8][9][10] as shown with sildenafil, vardenafil and tadalafil. 9,11,12 Lodenafil carbonate is a new dimeric PDE5 inhibitor structurally related to sildenafil and bearing a carbonate bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported antinociceptive effects of PDE5A inhibitors, such as sildenafil, tadalafil and vardenafil, in various rodent pain models including diabetic neuropathy (Gediz, Nacitarhan et al, 2015;Jain, Patil et al, 2001;Otari & Upasani, 2015;Patil, Jain et al, 2004;Wang, Zhao et al, 2017). Considering that single-cell RNA-sequencing analyses failed to detect significant PDE5A expression in somatosensory neurons (Usoskin, Furlan et al, 2015;Zeisel, Hochgerner et al, 2018), an altered vascular function might be one reason for the observed behavioural effects.…”
Section: Somatosensory Functions Of Cng Channels and Pdesmentioning
confidence: 99%
“…Other investigators reported the beneficial effect of NO when combined with gabapentin despite the different experimental conditions employed (Curros-Criado and Herrero, 2009). Similarly, Huang et al (2015) documented the analgesic effects of an NO-donating derivative in a rat model of PDN, and Otari and Upasani (2015) reported on the involvement of NO-cGMP signaling in neuropathic pain processing.…”
Section: Introductionmentioning
confidence: 98%